Effect of Atmospheric Attenuation on Laser Communications for Visible and Infrared Wavelengths - Ali, Mazin Ali Abd; Mohammed, Miami Abdulatteef (Al-Nahrain Journal of Science, 2018)
A theoretical study and analysis of the effect of some weather parameters on the laser light source of optical signal in free space (FSO), were discussed. The effect of these parameters on attenuation coefficient of the laser beam was calculation at wavelengths (650, 785 and 1550) nm. The attenuation coefficient was (0.698, 0.546 and 0.225) dB/km for wavelengths (650, 785 and 1550) nm respectively at a visibility of 20 km. We studied as well the receiver optical power, data transfer rate and link margin under the influence of the weather conditions. It was found that weather conditions such as (clear, haze, thin fog, light fog, heavy fog) effect on those wavelength at different ways. It is feasible to enhance the system performance such as link range and data transfer rate by increasing transmitting power and decreasing laser beam divergence angle.